Konstruksi Yuridis dan Implikasi Hukum PPPK Paruh Waktu dalam Sistem Kepegawaian Negara Indonesia - Emirza Nur Wicaksono (Indonesian Journal Publisher, 2025)
This study aims to analyze the juridical construction and legal implications of the part-time Government Employees with Work Agreements (PPPK) status within Indonesia’s national civil service system, based on the latest regulations, particularly Law No. 20 of 2023 on State Civil Apparatus and its implementing regulations. The study identifies normative ambiguities that result in legal uncertainty and potential violations of administrative law principles and employee rights protection. A normative juridical research method was used, involving the analysis of statutory documents and relevant legal literature. The findings reveal that part-time PPPK arrangements lack a clear and robust legal basis at the statutory level, hindering fair and consistent implementation. The absence of adequate regulation leads to weak protection of employee rights and disparities in implementation across the field. Therefore, this study recommends strengthening the legal framework through revisions to State Civil Apparatus Law and the issuance of comprehensive implementing regulations that explicitly govern the legal status and protections of part-time PPPK employees. This is essential to uphold the principles of legal certainty and justice in the national civil service system. The findings offer a new perspective for developing a more inclusive and responsive civil service policy in the era of bureaucratic reform